IoT Based Smart Garage Application Design for Residential Residences - Tiara Rabbani; Suhartono; Abd Rahman Patta (International Journal of Technology and Education Research, 2026)
The rapid development of the Internet of Things (IoT) has encouraged the adoption of smart technologies in residential environments, including garage management systems. However, existing smart garage solutions primarily emphasize remote control functionality while providing limited support for enhanced security, activity monitoring, and user management. This study aims to design and evaluate an IoT-based Smart Garage application that improves both convenience and security for residential users. The research adopts a Research and Development (R&D) approach using the Agile software development methodology. The proposed application integrates remote garage control, real-time status notifications, activity history tracking, user profile management, and biometric authentication through Android Keyguard Manager. System quality was evaluated based on the ISO 25010 standard, focusing on functional suitability, usability, and reliability. The results indicate that the application achieved a functional suitability score of 100%, demonstrating that all implemented features operated according to requirements. Usability testing using the System Usability Scale (SUS) produced an average score of 80, indicating acceptable user satisfaction and ease of use. Reliability testing confirmed stable system performance without failures during continuous operation. The study contributes a secure and integrated smart garage framework by combining IoT-based control, activity monitoring, and device-level biometric authentication within a single mobile application.